PENGARUH KUALITAS PELAYANAN, HARGA DAN KUALITAS MAKANAN TERHADAP KEPUASAN PELANGGAN DI RESTORAN BUNAKEN - Adariang Giawa; Yossi Hendriati (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2022)
This research aims to determine the effect of price service quality on customer satisfaction at Bunaken restaurants. There is also a research method is a quantitative method. The population in this study are regular customer of Bunaken restaurant. Data collection instrument using a questionnaire whit a sample of 45 respondents. Based on the results of research, service quality has no significant effect on customer satisfaction whit a t value of (1.615) sig (0.060), price has no effect on customer satisfaction whit a t value of (- 1.286)sig (0.206) while food quality has a significant effect on customer satisfaction at Bunaken restaurants whit a t value of (3.022) sig (0.004). simultaneously has a signifikan effect whit the calculated f value of (5.936) sig (0.002). the result of the value of R Square (R) = 0,303, from these results it can be concluded that the variables of service quality (X1), price (X2) and food quality (X3) simultaneously affect the customer satisfaction variable by 30,3% while the remaining 69,7% is influenced by other variables outside this regression equation or variables that not investigated by the authors